Making landscape public : making public landscape - Notteboom, Bruno, 1973-; Dehaene, Michiel, 1971-; Teerds, Hans, 1976- (Rotterdam : NAi, 2014)
OASE 93 examines the recent attention that has been paid to the relationship between landscape and urban planning. This issue explores historical and contemporary attempts at defining landscape as a public project, as well as the new constellations of government, designer, and citizen that go along with this process. It also discusses the media in which landscapes are depicted for a broad audience: television programmes, atlases, exhibitions, and cultural events. Just about all aspects of urban planning and architecture have been framed in recent years as landscape: housing, recreation, heritage, and water issues. Whereas the 1990s reflected a landscape of unbridled possibilities, today the focus is on redevelopment and sustainability. The social challenge incumbent on the landscape is great. Both a clear public project and economic support are lacking, and the government often refuses to take notice. These absences are filled by the small scale, and by forms of new commons. But what is landscape without a public conversation about it? To get this conversation started, OASE goes beyond the socio-historical consensus.
Dutch and English.
Van Gerrewey, Christophe
Keywords: City planning -- Philosophy; Landscapes -- Philosophy; Landscapes -- Social aspects; Landschap; Landschapsarchitectuur; Landschapszorg